STUDY OF TEETH HARD TISSUES STATE IN CHILDREN WITH DELAYED TEETH ERUPTION - Horokhovskyi, V.V.; Dienha, O.V.; Schnayder, S.A. (World of Medicine and Biology, 2020)
The results of the study are evident of high prevalence of the carious process in children with delayed tooth eruption: in children of 7 years old – 93.55 %, in children of 8 years old – 100 %. The intensity of decay of the deciduous teeth according to the decayed and filled teeth index in children of the main group of 7 years old was 4.68±0.35, in children of 8 years old – 4.94±0.23. The intensity of the carious process in the permanent teeth in children of the main group of 8 years according to the decayed, filled, and missing teeth index was 0.74±0.08. The data obtained are evidence of a higher prevalence and intensity of dental caries in children with delayed tooth eruption compared with indices of children whose tooth eruption occurred at term.